Pengaruh Komposisi Daun Gamal (Gliricidia sepium Hbr.) dan Kotoran Sapi dengan Nutrisi Pisang terhadap Rasio C/N Kompos - Sedo, Karolina M.; Tawa, Bibiana Dho; Lulan, Theodore Y. K.; Gauru, Imanuel; Cunha, Theodorus M. Da (Chemistry Notes, 2021)
It has been done a research on the effect of the composition of gliricidia sepium Hbr. And cow dung with banana nutrition on the composting process on the C/N ratio. This research was conducted with the aim of knowing the effect of the composition and the length of time required for fermentation. Composting was made with a variety of cow dung : gliricidia sepium Hbr. In a ratio of 1:9, 1:1, 3:2, 7:3, 9:1, and 2:3 in % by using 25% banana nutrition and 100% water from the total weight of the manure. On this research was found that the optimal time is on 14th day with characteristic of compost that was produced, equal with the the Indonesia National Standar (SNI Kompos 19-7030-2004). The conclusion is the compcsition of cow dung and Gliricidia sepium leaves did not significant affect to the C/N compost ratio.